Microwave Pyrolysis of Biomass: The Influence of Surface Area and Structure of a Layer; Applied Sciences; Vol. 12, iss. 23 - Kurgankina M. A. Margarita Aleksandrovna; Nyashina G. S. Galina Sergeevna; Shvets A. S. Anatoly Sergeevich; Vershinina K. Yu. Kseniya Yurievna; Pereira Junior A. O. Amaro Olimpio (2022, 2022)
Title screen